(untitled) (Diametros, 2020)
Many psychologists have tried to reveal the formation and processing of moral judgments by using a variety of empirical methods: behavioral data, tests of statistical significance, and brain imaging. Meanwhile, some scholars maintain that the new empirical findings of the ways we make moral judgments question the trustworthiness and authority of many intuitive ethical responses. The aim of this special issue is to encourage scholars to rethink how, if at all, it is possible to draw any normative conclusions by discovering the psychological processes underlying moral judgments.